The scoping review of depression and suicidal ideation among police and front-liners - Noor Azeiah Che Sat; Nor Ba’yah Abdul Kadir; Rusyda Helma Mohd; Hilwa Abdullah @ Mohd Nor (Penerbit Universiti Kebangsaan Malaysia, 2025)
Police and other front-liners (e.g., firefighters, paramedics, first responders, law enforcers) constitute unique jobs that require sacrifices in many situations when undertaking their duties and often lead to mental health issues including depression. Suicidal ideation is among the worrying risk factors that can result from depression. Thus, it is crucial to understand the relationship between depression and suicidal ideation and the risk factors involved, and their implications for police and front-liners. This scoping review was designed to identify studies examining depression and suicidal ideation among police and front-liners as well as the risk factors. A scoping review search was conducted using Google Scholar, PubMed, SAGE Journal, SCOPUS, Elsevier, APA, and JSTOR databases. The initial database search returned 2,240 articles. Following the review and scoping only 33 studies were selected based on the inclusion criteria before being manually extracted and independently screened by two reviewers. Participants in the articles were primarily police officers or law enforcers, with few articles involving firefighters, paramedics, and other first responders. Most studies were quantitative and the systematic literature reviews focused on depression, suicide, mental health, work, and traumatic stress. Recognizing the risk factors of depression and suicidal ideation and their dynamic association helps provide police officers and other front-liners with a perspective of the psychological challenges in their job. Further research is needed to better understand the risk factors and suggest protective adaptive strategies and programmes to promote mental health among police and front-liners.